Desain bahan ajar kontekstual terintegrasi strategi multi representasi pada materi pengukuran besaran fisika dan vektor dalam fisika kelas X SMA/MA - Adek Mauizah; Amali Putra (Universitas Negeri Padang, 2019)
Based on the results of observations at SMAN 1 Bukittinggi obtained low student learning outcomes. One of the causes of low student grades is indicated because students are less able to represent knowledge from one form to another, for example into a chart / table / diagram / picture form. Low learning outcomes also show that the lack of physics teaching materials that can connect learning with various contexts that exist around students. The purpose of this study is to produce integrated contextual teaching materials for multi-representation strategies that are worth seeing from the validation of experts and practicality.This type of research is the Research and Development (R&D) model of Sugiyono. The validation test was conducted by three lecturers of Physics FMIPA UNP. The practicality test was conducted by two practitioners / teachers who taught at SMAN 1 Bukittinggi and 34 students of class X. Based on data analysis conducted and obtained input on improving teaching materials, obtained teaching materials that were valid and practical were in accordance with the eligibility criteria of validity and practicality.